PSO-based PID controller for frequency control of two area interconnected power system - Dumre, Sandip; Pun, Purna Bahadur (Himalayan Journal of Applied Science and Engineering, 2025)
This paper presents an analysis of the dynamic performance of frequency control in a two-area interconnected power system using a Particle Swarm Optimization (PSO)-based PID controller. Maintaining stable system frequency within specified limits is crucial for the efficient operation of power system equipment. The proposed power system model comprises synchronous generators, loads in two distinct areas, and a photovoltaic (PV) system in Area-1. The system is modeled in MATLAB Simulink to analyze the impact of load variations and PV generation on system frequency. PSO, an evolutionary optimization technique, is employed to determine the optimal PID controller gains, minimizing frequency deviations. Three load increase scenarios in the two-area system were considered to evaluate the performance of the proposed controller. The results demonstrate the effectiveness of the PSO-based PID controller in mitigating frequency deviations, enhancing system stability and reliability. This study provides valuable insights into automatic optimal tuning of PID controllers in two-area systems, contributing to improved stability and operational reliability in power systems.